Nasal carriage rate, associated factors, and antimicrobial susceptibility patterns of methicillin resistance Staphylococcus aureus among pre-clinical undergraduate students at the College of Health and Medical Sciences, Haramaya University, Ethiopia - Weldegebreal, Fitsum; Urgesa, Kedir; Ayele, Firayad; Bogale, Kasahun; Shume, Taddese; Ahmed, Mohammed; Debebe, Sileshi; Tebeje, Fikru; Asmerom, Haftu; Tesfa, Tewodros; Mekonnen, Shambel (Frontiers in Public Health, 2024)
Background: Staphylococcus aureus nasal carriage linked to higher rates of infection and morbidity. People with methicillin-resistant S. aureus can be a potential source of infection for others. University students living together in crowded conditions increase their risk of acquiring infections. The prevalence methicillin-resistant S. aureus , in Ethiopian university students is sparse. Objective: To determine the nasal carriage rate, associated factors, and antimicrobial susceptibility patterns of methicillin-resistant Staphylococcus aureus among pre-clinical students at the College of Health and Medical Sciences, Haramaya University, Ethiopia, from July 1 to August 30, 2022. Methods: An institutional-based cross-sectional study was conducted among 270 randomly selected pre-clinical Health and Medical Sciences students. Data were collected using pre-tested, structured questionnaires. A nasal swab was taken from each participant and sent to the microbiology laboratory via Amie's transport media in a cold chain. There, it was cultivated using conventional techniques. The isolated colonies were S. aureus, and it's antimicrobial susceptibility was performed using Kirby-Bauer disc diffusion method on Muller-Hinton agar. Methicillin-resistant. S. aureus expressing using cefoxitin based on CLSI breakpoint. Data were entered into Epi-Data version 4.4.2.1 and exported to the Statistical Package for Social Sciences (SPSS) software version 25 for analysis. Pearson chi-square test was performed to predict the associations between variables. A p-value less than 0.05 was regarded as statistically significant. Result: Methicillin-resistant S. aureus nasal carriage was 5.9% (95% CI: 3.09–8.7) of cases of S. aureus nasal colonization, which was found to be 12.96% (95% CI: 8.85–16.96). Methicillin-resistant S. aureus nasal colonization was significantly associated with history of cigarette smoking (p = 0.000), intake of Kchat (p = 0.042), nose-picking habit (p = 0.003), sharing personal goods (p = 0.021), and hospitalizations (p = 0.00). All of the methicillin-resistant S. aureus were resistant to ampicillin and cefoxitin. Conclusion: Based on the finding, considerable proportion of healthy students harbored methicillin-resistant S. aureus, associated with behavioral factors. Furthermore, these isolates showed high resistance to cefoxitin and ampicillin. Hence, it is crucial to regularly test preclinical students to prevent endogenous infections and spread of methicillin-resistant S. aureus. Keywords: Nasal carriage, Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, students, Harar